2021
DOI: 10.1038/s42003-021-01711-3
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic and in-gel analysis of maleic acid co-polymer nanodiscs reveals differences in composition of solubilized membranes

Abstract: Membrane proteins are key in a large number of physiological and pathological processes. Their study often involves a prior detergent solubilization step, which strips away the membrane and can jeopardize membrane protein integrity. A recent alternative to detergents encompasses maleic acid based copolymers (xMAs), which disrupt the lipid bilayer and form lipid protein nanodiscs (xMALPs) soluble in aqueous buffer. Although xMALPs are often referred to as native nanodiscs, little is known about the resemblance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…The identification and quantification of lipids in nanodiscs, as shown here, is of particular interest for two reasons: First, the integration of different lipid classes and species into the nanodiscs during its assembly has to be carefully evaluated and verified to ensure that the desired membranes are used for subsequent experiments. Second, nanodisc polymers can be employed to solubilize natural lipid membranes; the identification and quantification of the lipid content in these membrane sections provides valuable insights into the composition of the natural membranes, including, for instance, the lipid environment of specific membrane proteins [24] . The analysis of the lipid content of nanodiscs was previously assessed by high‐resolution native MS [25] .…”
Section: Resultsmentioning
confidence: 99%
“…The identification and quantification of lipids in nanodiscs, as shown here, is of particular interest for two reasons: First, the integration of different lipid classes and species into the nanodiscs during its assembly has to be carefully evaluated and verified to ensure that the desired membranes are used for subsequent experiments. Second, nanodisc polymers can be employed to solubilize natural lipid membranes; the identification and quantification of the lipid content in these membrane sections provides valuable insights into the composition of the natural membranes, including, for instance, the lipid environment of specific membrane proteins [24] . The analysis of the lipid content of nanodiscs was previously assessed by high‐resolution native MS [25] .…”
Section: Resultsmentioning
confidence: 99%
“…One study reported no differences in lipid content between SMALPs and the originating E. coli membrane [ 72 ], whereas subtle differences were observed between total membrane and SMA solubilised samples for Pichia pastoris expressing CD81 [ 22 ]. Lipidomic analysis of nanodiscs generated using a variety of polymers, including SMA and DIBMA, suggested that glycerolipids are strongly enriched and phospholipids de-enriched in polymer-solubilised samples compared with the originating E. coli and Jurkat membranes [ 75 ]. In model heterogenous phase-separated bilayers, SMA preferentially solubilised lipids in the fluid phase [ 76 ], suggesting that biological membrane microdomains with differing fluidity may be differentially soluble in SMA.…”
Section: Protein–lipid Interactionsmentioning
confidence: 99%
“…These factors, collectively, influence polymer-polymer, polymer-lipid, protein-polymer interactions, which may compromise the yield, purity, activity of final purified target protein, and thus the downstream analyses. Not to mention that different polymers have shown to display differential preference for solubilization of specific types of lipids in biomembranes derived from prokaryotes and eukaryotes [ 58 ]. As demonstrated by multiple lines of research, the lipid composition of polymer-based nanodiscs is inevitably susceptible to change through inter-particle collision.…”
Section: Synthetic Polymers For Reconstitution Of Membrane Assembliesmentioning
confidence: 99%